Vitex agnus-castus Extracts for Female Reproductive Disorders: A Systematic Review of Clinical Trials - van Die, M. Diana; Burger, Henry G.; Teede, Helena J.; Bone, Kerry M. (Planta Medica, 2013)
Vitex agnus-castus L. (chaste tree; chasteberry) is a popular herbal treatment, predominantly used for a range of female reproductive conditions in Anglo-American and European practice. The objective of this systematic review was to evaluate the evidence for the efficacy and safety of Vitex extracts from randomised, controlled trials investigating womenʼs health.Eight databases were searched using Latin and common names for Vitex and phytotherapeutic preparations of the herb as a sole agent, together with filters for randomised, controlled trials or clinical trials. Methodological quality was assessed according to the Cochrane risk of bias and Jadad scales, as well as the proposed elaboration of CONSORT for reporting trials on herbal interventions.Thirteen randomised, controlled trials were identified and twelve are included in this review, of which eight investigated premenstrual syndrome, two premenstrual dysphoric disorder, and two latent hyperprolactinaemia. For premenstrual syndrome, seven of eight trials found Vitex extracts to be superior to placebo (5 of 6 studies), pyridoxine (1), and magnesium oxide (1). In premenstrual dysphoric disorder, one study reported Vitex to be equivalent to fluoxetine, while in the other, fluoxetine outperformed Vitex. In latent hyperprolactinaemia, one trial reported it to be superior to placebo for reducing TRH-stimulated prolactin secretion, normalising a shortened luteal phase, increasing mid-luteal progesterone and 17β-oestradiol levels, while the other found Vitex comparable to bromocriptine for reducing serum prolactin levels and ameliorating cyclic mastalgia. Adverse events with Vitex were mild and generally infrequent. The methodological quality of the included studies varied, but was generally moderate-to-high. Limitations include small sample sizes in some studies, heterogeneity of conditions being treated, and a range of reference treatments.Despite some methodological limitations, the results from randomised, controlled trials to date suggest benefits for Vitex extracts in the treatment of premenstrual syndrome, premenstrual dysphoric disorder and latent hyperprolactinaemia. Further research is recommended, and greater transparency in reporting for future trials.
Keywords: Vitex agnus-castus; Verbenaceae; premenstrual; mastalgia; hyperprolactinaemia; systematic review